Improved method to reduce interfacial defects in bonding polydimethylsiloxane layers of microfluidic devices for lab–on–chip applications (Superficies y Vacío, 2017)
This work describes a method to achieve a nearly seamless bonding between two polydimethylsiloxane (PDMS) surfaces. This material is widely used to realize microfluidic systems, and obtaining a strong union is an important step in the fabrication process. From the proposed bonding method, a minimal interface is accomplished, useful for hermetic seals in microfluidic systems. The presented method relies in the surface activation by oxygen plasma and the interaction of said treated surface with uncured PDMS. A comparison of bonding methods is presented in this paper in order to assess the performance of the bonding process and verify the interface formed between the bonded surfaces. The intended application of the presented method is the fabrication of pressure sensors, micropumps, microchannels, microfluidic pumps, valves, mixers and other structures that demand a complete seal over the bonded surfaces.